Think Pair Share Cooperative Learning and Changes in Student Learning Motivation in Secondary Education - Amalia Ramadani; Muhammad Yany; Sandi (EduLine: Journal of Education and Learning Innovation, 2026)
This study investigates the effect of applying the Think Pair Share (TPS) type of cooperative learning model on students' learning motivation. This study employs a quantitative approach with a pre-experimental design using the One Group Pretest-Posttest Design. The sample consisted of 46 eighth-grade students of SMP Al-Islam Wellulang, determined through a saturated sampling technique. Data were collected using a learning motivation questionnaire and analyzed through descriptive and inferential statistics, including the Shapiro-Wilk normality test and the Wilcoxon Signed Rank Test. The results show that students' learning motivation before treatment was in the moderate category with a mean score of 43.60, while after the implementation of the Think Pair Share model the mean score increased to 81.55, which falls into the high category. The Wilcoxon Signed Rank Test produced a significance value below 0.05, indicating a significant difference between the pretest and posttest scores. The findings of this study suggest that the cooperative learning model of the Think Pair Share type effectively enhances students' learning motivation by encouraging independent thinking, paired discussion, and whole-class sharing, thereby creating a more active, interactive, and student-centered learning atmosphere.